2020
DOI: 10.1089/mdr.2019.0344
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Sequences Included in Transmission Clusters Within Newly Diagnosed HIV-1 Patients in Southern Spain (2004–2015)

Abstract: The presence of transmission clusters (TCs) and their epidemiological characteristics in a treatment-naive cohort of HIV-1 patients in southern Spain over a decade (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) were evaluated. Protease and reverse transcriptase sequences provided by each genotype test were used in the phylogenetic study, performed first by the neighbor-joining method and then confirmed by Bayesian analysis. We collected clinical, immunovirological, and demographic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
3
3
0
Order By: Relevance
“…This can be related to the low percentage of migrants in Galicia, who have a reduced association to TCs, and the high number of patients belonging to the large F1_1 TC, currently comprising 205 individuals, which has successfully spread in Galicia and other Spanish regions (Delgado et al, 2015), even in other European countries (Delgado et al, 2015;Vinken et al, 2019). We have found an association of young patients (age range 20-29 years) to TCs in Galicia, similarly to the findings in other studies (Brenner et al, 2017;Dennis et al, 2018;Fabeni et al, 2019;González-Domenech et al, 2020;Paraskevis et al, 2019;Verhofstede et al, 2018), but not in the Basque Country. Public health interventions for reducing high risk behavior and control measures in this age group in Galicia should be implemented to decrease HIV-1 transmissions in the region.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This can be related to the low percentage of migrants in Galicia, who have a reduced association to TCs, and the high number of patients belonging to the large F1_1 TC, currently comprising 205 individuals, which has successfully spread in Galicia and other Spanish regions (Delgado et al, 2015), even in other European countries (Delgado et al, 2015;Vinken et al, 2019). We have found an association of young patients (age range 20-29 years) to TCs in Galicia, similarly to the findings in other studies (Brenner et al, 2017;Dennis et al, 2018;Fabeni et al, 2019;González-Domenech et al, 2020;Paraskevis et al, 2019;Verhofstede et al, 2018), but not in the Basque Country. Public health interventions for reducing high risk behavior and control measures in this age group in Galicia should be implemented to decrease HIV-1 transmissions in the region.…”
Section: Discussionsupporting
confidence: 92%
“…HIV-1 molecular epidemiological studies in different countries, independently of the methodology used, have found a similar association(Duran-Ramirez et al, 2021; Parczewski et al, 2017;Wertheim et al, 2017). Also, studies in other Spanish regions have found this association of TCs with MSM(González-Domenech et al, 2020;Pérez-Parra et al, 2015). These findings indicate that MSM TCs are playing a main role in spreading HIV-1 infections and are consistent with the fact that MSM is the main frequent mode of HIV-1 transmission in Spain since the early 2000(Nuñez et al, 2018).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…HIV-1 molecular epidemiological studies in different countries, independently of the methodology used, have found a similar association ( Parczewski et al, 2017 ; Wertheim et al, 2017 ; Ramirez et al, 2021 ). Also, studies in other Spanish regions have found this association of TCs with MSM ( Pérez-Parra et al, 2015 ; González-Domenech et al, 2020 ). These findings indicate that MSM TCs are playing a main role in spreading HIV-1 infections and are consistent with the fact that MSM is the main frequent mode of HIV-1 transmission in Spain since the early 2000s ( Nuñez et al, 2018 ).…”
Section: Discussionsupporting
confidence: 52%
“…Spanish clinical guidelines recommend to perform a genotypic drug resistance test before starting antiretroviral therapy (ART) in all HIV-1-diagnosed patients and in ART-failing cases [ AIDS study group (GESIDA) of the Spanish Society of Infectious Diseases and Clinical Microbiology and the National AIDS Plan, 2020 ]. Pr-RT sequences obtained for these tests have been analyzed in different molecular epidemiology studies, describing the genetic features of the HIV-1 epidemic in different regions of Spain ( Thomson et al, 2001 ; Holguín et al, 2007 ; Cuevas et al, 2009a , b ; González-Alba et al, 2011 ; Yebra et al, 2013 ; Pérez-Parra et al, 2015 , 2016 ; Patiño-Galindo et al, 2016 , 2017b ; González-Domenech et al, 2020 ). The phylogenetic studies have also allowed the identification of large TCs among MSM which are actively growing in Spain ( Delgado et al, 2015 , 2019 ; Patiño-Galindo et al, 2017a ; González-Domenech et al, 2018 ), as well as transmitted drug resistance mutations which are spreading in TCs ( Cuevas et al, 2009b ; Vega et al, 2015 ; Viciana et al, 2016 ; González-Domenech et al, 2018 , 2020 ), highlighting the value of molecular epidemiology as a tool for HIV surveillance.…”
Section: Introductionmentioning
confidence: 99%